METHODS OF IMPROVING READING HABITS AND SKILLS IN THE PRIMARY STAGES OF TEACHING ENGLISH (Academicia Globe: Inderscience Research, 2021)
This article discusses the importance of teaching and learning foreign language. It studies the fairy tales as an important means of teaching foreign language in the primary stages of school.